2013
DOI: 10.4172/2329-6925.1000112
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Large and Giant Paraclinoid Internal Carotid Artery Aneurysms

Abstract: Paraclinoid internal carotid artery aneurysms originate from the internal carotid artery between the distal dural ring and the posterior communicating artery. Surgical treatment of these aneurysms is technically challenging because of the surrounding neurovascular structures. There are several ways to treat these lesions: direct clipping with retrograde suction decompression, endovascular coiling, coiling with stent, and flow diverter stent. Here, I briefly review the surgical and endovascular options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Both treatments carry a risk of morbidity and mortality. In this context, it is suggested that the treatment of this pathology occur in centers with a high flow of cases and high experience in the management and choice of the most appropriate treatment [2,[4][5][6][7][8]. The treatment of this pathology is complex and requires strict, meticulous planning before treatment, as described previously in our paper and based on the articles.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Both treatments carry a risk of morbidity and mortality. In this context, it is suggested that the treatment of this pathology occur in centers with a high flow of cases and high experience in the management and choice of the most appropriate treatment [2,[4][5][6][7][8]. The treatment of this pathology is complex and requires strict, meticulous planning before treatment, as described previously in our paper and based on the articles.…”
Section: Discussionmentioning
confidence: 90%
“…New studies may allow greater precision and resolution. It is a non-invasive technique that may provide benefit for the diagnosis of these patients [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by van Rooij et al [25], it is found that nearly all giant aneurysms show reopening after endovascular treatment in the 6-month postoperative period, even up to several years of stable condition. The follow-up strategy for these patients is to schedule additional coiling procedures along with routine follow-up, with decreased patient compliance as a result [25,37]. MRA has also been suggested as a routine follow-up procedure after endovascular treatment [37].…”
Section: Endovascular Approachmentioning
confidence: 99%
“…The follow-up strategy for these patients is to schedule additional coiling procedures along with routine follow-up, with decreased patient compliance as a result [25,37]. MRA has also been suggested as a routine follow-up procedure after endovascular treatment [37].…”
Section: Endovascular Approachmentioning
confidence: 99%